AN IN SILICO APPROACH FOR THE EVALUATION OF CELL WALL COMPONENTS OF PROBIOTICS AS BIOLOGICAL ADSORBERS OF AFLATOXINS - P. Jalantha; Ganne Venkata Sudhakar Rao; N. Pazhanivel; M. Parthiban; P. Veeramani; M.R. Srinivasan; C. Soundararajan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Aflatoxins are produced in poultry feed by two major fungal species viz., Aspergillus flavus and Aspergillus parasiticus during hot and humid seasons. To detoxify these aflatoxins, various binders are being used in the field which are mostly synthetic compounds with possible other toxicities, the harmless beneficial probiotics are being considered as binders to neutralize the effect of aflatoxins in the feed. Bacterial organisms (probiotics) like Lactobacillus rhamnosus, Lactobacillus casei, Bacillus subtilis, Enterococcus faecium and yeast (Saccharomyces cerevisiae) were selected and their cell wall structures have been retrieved and molecular docking was performed against four types of aflatoxins namely AFB1, AFB2, AFG1 and AFG2. The results revealed that cell wall components of the chosen bacterial organisms have a good binding affinity towards four types of aflatoxins. Based on this in silico results, it is evident that the both the lipoteichoic acid (LTA) and wall teichoic acid (TA) in the cell wall of probiotic organisms is responsible for its binding against aflatoxins.